ALGORITHM FOR DETERMINING THE TORQUE OF ELECTRIC MOTORS USING INDIRECT MEASUREMENT METHODS - KVASHUK, Dmytro; YASHCHUK, Olesia (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Indirect torque measurement methods can be performed in a variety of ways, depending on the specific situation and available tools. One such way is to measure the displacement, or speed of rotation of the shaft and use this information to calculate the moment using the moment of inertia equation. For this, it is necessary to know the moment of inertia and the angular acceleration, which can be measured using a gyroscope or accelerometer. Another way is to measure the voltage and current in the electrical circuit connecting the motor and the power source by determining the power of the electric motor.However, indirect methods of measuring torques of electric motors are based on the measurement of other physical parameters that correlate with torque, such as current, voltage, rotation frequency, etc. These methods are often used because of their cost-effectiveness and ease of implementation, but they have some drawbacks. In particular: indirect methods are usually less accurate than direct methods because they depend on mathematical models and correlations between different parameters, which may be imprecise or incomplete; parameters that are measured by indirect methods may be influenced by external factors, which may affect the accuracy of measurements; calibration of devices is usually carried out in laboratory conditions, so the results may not reflect real operating conditions; the mathematical models used to determine the torque may be non-linear. This can lead to errors in measurements, especially at high or low torque values; indirect methods do not provide direct feedback about the real torque, which can lead to delays in process regulation and control. This can be critical for some applications where fast and accurate torque control is essential; indirect methods may be less efficient or unsuitable for some types of electric motors or applications. For example, when using high-frequency or multiphase motors, indirect methods may not provide sufficient accuracy or stability of measurements. The article examines algorithms for determining the rotational parameters of electric motors using indirect measurement methods. An analysis of the characteristics of electric motors according to their energy data was carried out. The measurement possibilities are determined based on the functional dependence of the torque on the power of the electric motor and the speed of rotation of its shaft. The characteristics of the power components are studied and the results of their simulation are given. An analysis of the methods of determining the angular velocity and angular acceleration of the electric motor shaft was carried out, and the role of these parameters in the determination of the torque was investigated. A two-channel network-type information and measurement system is proposed, which allows data collection and their visualization, where one channel is used to measure power, the other to measure shaft rotation speed.
Keywords: torque; angular velocity; electric motor; measurement system; data; measurement methods; sensors